The Effect of Counseling on Changes in Attitudes and Actions in Containing Covid-19 Vaccination in the Elderly at Unaaha Health Center, Konawe Regency - Maulana, Asrinda; Supodo, Timbul; Sunarsih, Sunarsih (Magister Kesehatan Universitas Mandala Waluya, 2022)
145 Introduction: Based on December 2021 data, the Public Health Center with the lowest COVID-19 vaccination coverage for the elderly was Unaaha Health Center which had a target of 2088 elderly people who had to be vaccinated with the coverage of the first dose of vaccination only 277 (16.1%) and the second dose of 119 vaccination (6,9%). This is what attracted researchers to conduct research on the Effect of Counseling on Changes in Attitudes and Actions in Conducting Covid-19 Vaccinations in the Elderly at the Unaaha Health Center, Konawe Regency. Method: This type of research is Pre Experiment, the research design that will be used is One Group Pretest-Posttest Design.This research was conducted in the working area of the Unaaha Public Health Center, Konawe Regency, Southeast Sulawesi Province, carried out in March 2022. While the sample used was 92 respondents. Result: Based on statistical tests, it is known that the exact sig (2-tailed) value shows a value of 0.000 <0.05 which means that there is a significant effect of counseling with the simulation method on changes in the attitude of the elderly and the exact sig (2-tailed) value shows a value of 0.000 <0.05 which means This means that there is a significant effect of counseling with the simulation method on changes in the actions of the elderly in carrying out Covid-19 vaccinations in the work area of the Unaaha Health Center. Conclusion: There is a significant effect between counseling with the simulation method on changes in the attitudes and actions of the elderly in carrying out Covid-19 vaccinations in the work area of ​​the Unaaha Health Center.